Isolation and molecular characterization of Fikirini rhabdovirus, a novel virus from a Kenyan bat - Kading, Rebekah C; Gilbert, Amy T; Mossel, Eric C; Crabtree, Mary B; Kuzmin, Ivan V; Niezgoda, Michael; Agwanda, Bernard; Markotter, Wanda; Weil, M Ryan; Montgomery, Joel M; Rupprecht, Charles E; Miller, Barry R (Journal of general virology, 2013)
Zoonotic and vector-borne pathogens have comprised a significant component of emerging human infections in recent decades, and bats are increasingly recognized as reservoirs for many of these disease agents. To identify novel pathogens associated with bats, we screened tissues of bats collected in Kenya. Virus isolates were identified by next generation sequencing of viral nucleic acid preparations from the infected cell culture supernatant and characterized. Here we report the identification of Fikirini rhabdovirus, a novel rhabdovirus isolated from a bat, Hipposideros vittatus, captured along the Kenyan coast.